2020
DOI: 10.1007/s00262-019-02470-1
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 in a TLR3- and 7/8-agonist-based DC maturation cocktail generates mature, cytokine-producing, migratory DCs but impairs antigen cross-presentation to CD8+ T cells

Abstract: Mature dendritic cells (DCs) represent cellular adjuvants for optimal antigen presentation in cancer vaccines. Recently, a combination of prostaglandin E 2 (PGE 2) with Toll-like receptor agonists (TLR-P) was proposed as a new standard to generate superior cytokine-producing DCs with high migratory capacity. Here, we compare TLR-P DCs with conventional DCs matured only with the proinflammatory cytokines TNFα and IL-1ß (CDCs), focussing on the interaction of resulting DCs with CD8 + T-cells. TLR-P matured DCs s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
0
9
0
1
Order By: Relevance
“…Gierlich et al have recently evidenced the importance of Poly(I:C) in combination with prostaglandin E2 and TLR7/8 agonist R848, in the maturation of DCs, which have a role in antigen presentation in cancer vaccines. The study showed that these DCs have high migratory ability and priming efficacy, together with increased cytokines production [67].…”
Section: Targeting Tlr3 and Therapy Resistancementioning
confidence: 97%
“…Gierlich et al have recently evidenced the importance of Poly(I:C) in combination with prostaglandin E2 and TLR7/8 agonist R848, in the maturation of DCs, which have a role in antigen presentation in cancer vaccines. The study showed that these DCs have high migratory ability and priming efficacy, together with increased cytokines production [67].…”
Section: Targeting Tlr3 and Therapy Resistancementioning
confidence: 97%
“…In contrast, the presence of PGE 2 in such cocktails may impair other DC functions. In particular, PGE 2 may limit cytokine production ( 30 , 33 ) and in a dose-dependent manner reduce cross-presentation ( 34 ). High levels of PGE 2 stimulation may even suppress DC migration ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the combination of Poly(I:C) and R848 with E7 DNA can induce the enormous regression of tumors, circulating antigen-specific IFN-γ and non-specific intratumoral IL-12 [67]. Similarly, Toll-like receptor agonists (TLR-P), Poly(I:C)/R848/PGE2, contribute to DCs with mature phenotypes and a brilliant ability to migrate and secrete cytokines, especially IL-12p70 production [68]. In the cancer therapy realm, work by Caisova and coworkers optimized therapeutic mixtures based on welldefined compounds, including the biocompatible anchor for the membranes (BAM) of mannan anchored to the surface of tumor cells, R848, poly(I:C), and lipoteichoic acid (LTA), leading to the eradication of advanced stage progressive melanoma in 83% of mice, the acquisition of resistance to tumor recurrence, and potential anti-metastatic effect [69].…”
Section: Combination Of Multiple Tlra For Tumor Therapymentioning
confidence: 99%